Architecture: History and Representation. Designing an Interactive Athlas. Proceedings and Communication (diségno, 2018)
Nowadays a qualitative leap is found in graphic production, a graphic discourse which is encouraged by new technologies and reproduction systems. There is a change in the visual grammars and we find a hyperinflation of the spreading of the new proposals in the new Information society. There is a need to construct a graphic and visual discourse on the Histor y of Architecture. We finf thata while postmodernsociety does not believe in a big history discourse, especially in Architecture; contemporary media demand for it, as Lyotard pointed out, in this commoditized society. Time has arrived to reflect on the capabilities new technologies and communication hold. We pretend to analyze thegraphic documentary as a language and as an effective mean to express and communicate Architecture History in the last half of the XX century, when different graphic production strategies were used. The documentary research, identification and cataloguing of the graphical material follow the production of Modern Architecture Atlas that consists of partial maps. This would be an interactive map suitable to be consulted from a different range of fields and categories; an Athlas capable to compare architects, art movements and architecture schools.
Keywords: Athlas; Technology; Communication; Representation; Information